The Cluster AgeS Experiment (CASE) – VIII. Age and distance of the Globular Cluster 47 Tuc from the analysis of two detached eclipsing binaries. Issue 3 (17th January 2020) - Thompson, I B; Udalski, A; Dotter, A; Rozyczka, M; Schwarzenberg-Czerny, A; Pych, W; Beletsky, Y; Burley, G S; Marshall, J L; McWilliam, A; Morrell, N; Osip, D; et al.
ABSTRACT: We use photometric and spectroscopic observations of the eclipsing binary E32 in the globular cluster 47 Tuc to derive the masses, radii, and luminosities of the component stars. The system has an orbital period of 40.9 d, a markedly eccentric orbit with e = 0.24, and is shown to be a member of or a recent escaper from the cluster. We obtain M_p = 0.862± 0.005 M_, R_p = 1.183± 0.003 R_, L_p = 1.65± 0.05 L_ for the primary and M_s = 0.827± 0.005 M_, R_s = 1.004± 0.004 R_, L_s = 1.14± 0.04 L_ for the secondary. Based on these data and on an earlier analysis of the binary V69 in 47 Tuc, we measure the distance to the cluster from the distance moduli of the component stars, and, independently, from a colour – surface brightness calibration. We obtain 4.55 ± 0.03 and 4.50 ± 0.07 kpc, respectively – values compatible within 1 σ with recent estimates based on Gaia DR2 parallaxes. By comparing the M – R diagram of the two binaries and the colour–magnitude diagram of 47 Tuc to Dartmouth model isochrones we estimate the age of the cluster to be 12.0 ± 0.5 Gyr, and the helium abundance of the cluster to be Y ≈ 0.25.